The Effectiveness of Criminal Law Supervison on Regional Employee Management in the Era of Autonomy - Berlian Evi Yenni Pakpahan; Ismaidar Ismaidar; Suci Ramadani (Journal Evidence Of Law, 2025)
The purpose of this study is to analyze the importance of legal supervision in maintaining regional personnel management in accordance with the merit system and the principles of good governance. The method used in this study is a normative juridical approach by examining relevant legislation, legal literature, and public administration doctrines. The results of the analysis show that the effectiveness of legal supervision plays an important role in preventing abuse of authority, nepotism, and the politicization of positions in local government. Effective legal supervision can strengthen performance-based civil service systems, increase the professionalism of the civil service, and ensure a clean and accountable bureaucracy.In conclusion, the application of effective legal supervision in regional personnel management is a fundamental requirement in the era of autonomy. Strong legal supervision is not only a means of controlling the implementation of regional authority, but also a means of fostering and strengthening the integrity of the apparatus in realizing good governance.